Factors Influencing Unmet Contraceptive Needs In Indonesia - Pika Novriani Lubis; Ratna Djuwita (Poltekkes Kemenkes Surakarta, 2022)
Background: As developing countries, family planning program services in Southeast Asia through 2019 are already excellent, with a user rate of 65% and a user satisfaction rate of 90%. However, Indonesia's unmet contraceptive need rate has remained stagnant for the last ten years. Methods: A systematic online search was carried out in four databases: Pubmed, EMBASE, Proquest, and Sage Journal, as well as Google Scholar. The keywords used were unmet need, gap, non-use, challenge, barrier, birth spacing, birth limiting, birth interval, pregnancy interval, fertility control, birth limiting, family planning, and contraception. A search was limited to articles written in English and Indonesian published in the recent five years, with the population setting its domicile in Indonesia. Selection data was guided by a PRISMA flow diagram and assisted by the specialized systematic review software Rayyan. Results: Of 571 articles, 7 matched the inclusion criteria and contained 32 unmet need associations. According to our findings, unmet contraceptive need in Indonesia is set by five factors: the level of the woman, the level of her partner, the level of the couple, the level of the household, and lastly, the level of the program or health services. Conclusion: Using a local language approach, invigorating family planning field officers, and embedding in premarital counseling and school education, this recent evidence can be used to renew the family program planning strategy and achieve the Sustainable Development Goals.